A survey of energy conservation techniques for mobile wireless communication devices - Chit, Suwannit Chareen (2016)
Mobile devices have undergone a tremendous evolution over the past two decades.Today, mobile devices are equipped with sensing, communication, computational and entertainment functionalities to deliver a myriad of services to its users.Running these functionalities, however, comes with a huge energy cost.In this paper, we survey general solutions for energy conservation in mobile devices.We classify and provide brief summaries of the energy conservation techniques based on their key research ideas. This paper will help researchers and designers to better understand the state-of-the-art in energy conservation in mobile devices.